Can Isotretinoin Induce Sacroiliitis: Three Cases - Ümit Dinçer,; Engin Çakar,; Mehmet Zeki Kıralp,; Hasan Dursun, (Archives of Rheumatology, 2008)
Our aim was to present three cases of retinoid-induced sacroiliitis demonstrated by magnetic resonance imaging and bone scintigraphy. Three patients with low back and hip pain, and lumbar stiffness after using isotretinoin for acne fulminans were described. Our cases were characterized by rapid resolution of pain and stiffness after isotretinoin treatment was discontinued. Although the association between isotretinoin therapy and sacroiliitis in arthritis patients was suggested in the literature it has not been clearly explained yet. Prospective studies are needed to reveal the causal relationship between isotretinoin and sacroiliitis. (Romatizma 2008; 23: 157-9)